Yes! We Can Teach and We Feel More Confident in Teaching: The Influence of Senior High School Teachers’ Demographic Variables on Their Self-Efficacy in Teaching - Opoku Adusei; Mercy Adwoa Eduam; Benjamin Praise Afeku; Samuel Kwabla Segbefia (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
It is generally accepted that a teacher's perception of efficacy correlates with the quality of instruction they offer. The purpose of this study was to determine the characteristics that senior high school (SHS) mathematics teachers in Ghana's Ashanti Region regard as the most influential in influencing their confidence in their abilities to teach their subject. It was requested that 154 senior high school teachers from 20 different senior high schools reply to a questionnaire containing 12 items. According to the results of an independent sample t-test, male teachers have significantly stronger self-efficacy views than their female colleagues. Again, the results of a one-way analysis of variance (ANOVA) test reveal that there was no statistically significant difference between the means of the five groups of teacher teaching experience in terms of teacher efficacy. Teachers should take part in ongoing professional development activities to make sure they are still good at their jobs.